The Analysis of Factors on Financial Distress in Property and Real Estate Manufacturing Companies Listed on the Bursa Efek Indonesia - Dinda April Yanti; Meigia Nidya Sari; Nur Aliah (ProBisnis : Jurnal Manajemen, 2023)
Only the property and real estate industry struggles with construction. Favourable regulatory structures have a significant influence on the development and expansion of the real estate and property industry. This study intended to analyze and determine the impact of the Current Ratio on Financial Distress in Manufacturing Companies in the Property and Real Estate Sector that are listed on Bursa Efek Indonesia. The data were empirical data obtained from the Bursa Efek Indonesia for 2015-2020 property companies. This research was conducted on the Bursa Efek Indonesia, specifically for property & real estate companies, using the website www.idx.co.id and other websites as required for data collection. 66 companies are listed on the IDX as real estate companies. Using the Eviews software, panel data analysis was employed to conduct this study's analysis. According to the results of the study, the regression coefficient of the current ratio is 0.223674, which is negative. It indicates that each addition of 1 unit to the current ratio, assuming all other variables remain constant, will increase financial distress by 0.223674. It is known that the t-count value t-table where 0.954656 2.0048, and that the probability value of the current ratio was 0.3439 > 0.05. Then, it can be concluded that the Current Ratio has a limited impact on the financial distress of companies in the Property & Real Estate sector that are listed on Bursa Efek Indonesia.